Rational Engineering of Chorismate-Related Pathways in Saccharomyces cerevisiae for Improving Tyrosol Production - Guo, Wei; Huang, Qiulan; Liu, Hao; Hou, Shaoli; Niu, Suhao; Jiang, Yi; Bao, Xiaoming; Shen, Yu; Fang, Xu (Frontiers in Bioengineering and Biotechnology, 2019)
Tyrosol is extensively used in the pharmaceutical industry as an important natural product from plants. In this study, an exogenous pathway involved in catalyzing tyrosine to tyrosol was introduced into Saccharomyces cerevisiae. Furthermore, The pyruvate decarboxylase gene pdc1 was deleted to redirect the flux distribution at the pyruvate node, and a bifunctional NAD+-dependent fused chorismate mutase/prephenate dehydrogenase from E. coli (EcTyrA) and its’ tyrosine inhibition resistant mutant (EcTyrAM53I/A354V) were heterologously expression in S. cerevisiae to tuning up the chorismate metabolism effectively directed the metabolic flux toward tyrosol production. Finally, the tyrosol yield of the engineered strain GFT-4 was improved to 126.74±6.70 mg/g DCW at 48 h, increased 440 times compared with that of the control strain GFT-0 (0.28±0.01 mg/g DCW). The new synergetic engineering strategy developed in this study can be further applied to increase the production of high value-added aromatic compounds derived from aromatic amino acid or shikimate in S. cerevisiae.